Moderate Ethanol Pre-treatment Mitigates ICH-Induced Injury via ER Stress Modulation in Rats - Lin, Peter Bor-Chian; Wang, Po-Kai; Pang, Cheng-Yoong; Hu, Wei-Fen; Tsai, Andy Po-Yi; Oblak, Adrian L.; Liew, Hock-Kean (Frontiers in Molecular Neuroscience, 2021)
Intracerebral hemorrhage (ICH) is a life-threatening type of stroke that disrupts the normal neurological function of the brain. Clinical studies have reported a non-linear J-shaped association between alcohol consumption levels and the occurrence of cerebral stroke. Specifically, alcohol intoxication increases stroke incidence, while moderate alcohol pre-conditioning decreases stroke frequency and improves outcomes. Although alcohol pre-consumption is likely a crucial player in ICH, the underlying mechanism remains unclear. We performed 1-hour alcohol pre-conditioning followed by ICH induction in Sprague Dawley (SD) rats to investigate the role of alcohol pre-conditioning in ICH. Interestingly, behavioral test analysis found that ethanol intoxication (3 g/kg) aggravated ICH-induced neurological deficits, but moderate ethanol pre-conditioning (0.75 g/kg) ameliorated ICH-induced neurological deficits by reducing the oxidative stress and proinflammatory cytokines release. Moreover, we found that moderate ethanol pretreatment improved the striatal ER homeostasis by increasing the chaperone protein expression and reducing oxidative stress and apoptosis caused by ICH. Our findings show that the mechanism regulated by moderate ethanol pre-conditioning might be beneficial for ICH, indicating the importance of ER homeostasis, oxidative stress, and differential cytokines release in ICH.